Development of a Basic Logic Gate Practicum Module to Support Quality Engineering Education in Digital Electronics - Sartika Anori; Syerlie Annisa; Ryan Fikri; Ganefri; Asmar Yulastri; Efrizon (Postgraduate, University of Mataram, 2026)
Meaningful learning in digital electronics requires hands-on practicum activities to support students’ understanding of abstract logic concepts. However, limited access to appropriate practicum media often hinders effective learning experiences. This study aims to develop and validate a physical Basic Logic Gate practicum module designed to support hands-on learning in digital electronics courses. The study employed a Research and Development approach using the 4D model, completing the Define, Design, and Develop stages up to expert validation and student practicality testing. The developed module consists of a hardware-based logic gate kit that enables students to assemble and test basic logic gate circuits directly during practicum sessions. Content and media validation were conducted by a material expert and a media expert using a Likert-scale instrument, while practicality testing involved 28 undergraduate students. The validation results indicated high validity, with scores of 96.19% from the material expert and 97.14% from the media expert. Practicality testing yielded an average score of 98.57%, indicating that the module is highly practical in terms of usability, functionality, and suitability for practicum implementation. These findings demonstrate that the developed Basic Logic Gate practicum module meets quality standards for instructional media and is feasible for use in digital electronics practicum learning.